(untitled) (Albayan Scientific Journal, 2023)
This study was conducted to investigate the impact of environmental conditions on wood formation, wood physical and anatomical properties of Pinus halepensisand Juniperus phoenicea trees growing at different altitudes in El- Jabal El-Akhdar region, Libya. Three tree species were randomly selected at each altitude. Some wood properties were determined, such as specific gravity, tracheid length, tracheid width (diameter), tracheid cell wall thickness, ray length (height), and its number (in tangential aspect). The results showed significant differences in wood properties among the trees of pine and juniper growing at the three altitudes. Also, the specific gravity, tracheid length and tracheid diameter, in altitudes (780m and 830m) showed the highest values when compared with the trees grown at the lowest altitudes (248m and 413m).